Effect of short-term caffeine supplementation on stress response and immune system of male athletes - Tofighi, A.; Ameghani, A.; Jamali, A.; Jamali Qarakhanlou, B. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Vigorous exercise stress might be leading cause of immune system disorders and appearance of acute and chronic inflammation in human body. Caffeine supplementation prior to exercise can be effective on body immune response. This study aimed to evaluate the effect of short-term caffeine supplementation on immune response and stress index in male athletes after an exhaustive aerobic exercise.